Importance of International Law for the Regulation of Domestic Work in Poland - Skupień, Dagmara (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
This article presents the main acts of international law and the jurisprudence of European courts that aim to ensure decent working conditions for domestic workers. The author analyzes the legal status of this group of workers in Poland from the times before the Second World War until now. The publication argues that Polish legislation should be complemented by specific provisions concerning domestic workers. The introduction of such measures to the Polish legal system is necessary to align national law with the ILO legal acts. Moreover, the author proposes that state financial incentives for natural persons employing domestic workers should be available in certain cases to encourage the legalization of this type of work.